Study on Coronary Arteries of Different Domestic Animals - Hareeswaraiah, M. (Indian Journal of Veterinary Anatomy, 2020)
The wall of the heart was supplied by right and left coronary arteries and their branches in all the domestic animals. The left coronary artery was usually larger and dominant in buffalo, sheep, goat, dog, whereas right coronary artery was dominant in pig. In dog were highly branched and consisted of rich network of capillary plexus when compared to other domestic animals. In ruminants, the coronary arteries of goat were highly branched than sheep and buffalo.